SOSIALISASI SISTEM MANAJEMEN KESELAMATAN RADIASI DI INSTALASI RADIOLOGI RUMAH SAKIT UMUM DAERAH PETALA BUMI - Yoshandi, T. Mohd.; Annisa, Aulia; Aprilia, Ghea (Awal Bros Journal of Community Development, 2025)
The radiation safety management system at the Radiology Installation of Petala Bumi Regional General Hospital is designed to protect patients, medical personnel, and the public from the risk of excessive radiation exposure. This system begins with the preparation of a radiation safety policy that serves as a guideline for every radiology procedure. In addition, risk identification and assessment are carried out at every stage of the radiology procedure to ensure that appropriate preventive measures can be implemented. The ALARA (As Low As Reasonably Achievable) principle is also applied to minimize the radiation dose received by patients and medical personnel, with the aim of keeping radiation exposure at the lowest possible level. In addition, medical personnel and hospital staff are given regular training on radiation safety procedures and the use of appropriate protective equipment to reduce risk. The radiology equipment used in this installation is also maintained and calibrated periodically to ensure that the equipment is functioning properly and does not provide excessive radiation doses. Monitoring of the radiation dose received by patients and medical personnel is also carried out regularly to ensure that all procedures remain in accordance with established safety standards. Overall, this radiation safety management system aims to maintain the safety and quality of radiology services, as well as ensure that the use of radiation is carried out safely and efficiently. This system is also evaluated and improved on an ongoing basis to ensure its effectiveness in reducing risks and improving safety standards in the hospital.